The Prevention of Positioning Injuries During Gynecologic Surgery. Guideline of the DGGG, OEGGG and SGGG (S2k Level, AWMF Registry Number 015/077, October 2020) - Fleisch, Markus C.; Bader, Werner; Balzer, Kai; Bennefeld, Luisa; Boeing, Carsten; Bremerich, Dorothee; Gass, Paul; Geissbuehler, Verena; Koch, Martin C.; Nothacker, Monika J.; Pietzner, Klaus; Renner, Stefan P.; Römer, Thomas; Roth, Stephan; Schütz, Florian; Schulte-Mattler, Wilhelm; Sehouli, Jalid; Lippach, Kristina; Tamussino, Karl; Teichmann, Alexander; Tempfer, Clemens; Thill, Marc; Tinneberg, Hans-Rudolf; Zarras, Konstantinos (Geburtshilfe und Frauenheilkunde, 2021)
Purpose Positioning injuries are relatively common, forensically highly relevant complications of gynecologic surgery. The aim of this official AWMF S2k-guideline is to provide statements and recommendations on how to prevent positioning injuries using the currently available literature. The literature was evaluated by an interdisciplinary group of experts from professional medical societies. The consensus on recommendations and statements was achieved in a structured consensus process.Method The current guideline is based on the expired S1-guideline, which was updated by a systematic search of the literature and a review of relevant publications issued between February 2014 and March 2019. Statements were compiled and voted on by a panel of experts.Recommendations The guideline provides general and specific recommendations on the prevention, diagnosis and treatment of positioning injuries.
Keywords: gynecologic surgery; positioning injuries; prevention